Alternative Film Soup Process in Creating Experimental Photography Works - Catyuriyanto, Setyo Tohari; Pratmajaya, FX. Purwastya; Rozak, Abullah (Institut Seni Indoensia Surakarta, 2025)
The purpose of this research is to create experimental photography works with alternative soup film processes. The target to be achieved in this research is to show that in creating experimental photography works with alternative soup film processes can produce scratches and spots of color composition that have an expressive impression. The steps that will be taken in creating this work are observation, brainstorming, exploration, experimentation and presentation of the work. This research can be used as a learning medium in the form of information on the stages of creating experimental photography works with the output of textbooks and journal articles.